2013
DOI: 10.7124/bc.000832
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of allelic variants of genes HLA-DRB1, HLA-DQA1, HLA-DQB1 and HLA-G among women with idiopathic recurrent pregnancy loss

Abstract: Aim. Analyze the distribution of allelic polymorphism of HLA-DRB1, DQA1, DQB1 genes and HLA-G 14-bp insertion/deletion polymorphism in women with RPL. Methods. DNA extraction, PCR, agarose gel electrophoresis. Results. A comprehensive analysis of the distribution and frequency of allelic variants of genes HLA-DRB1, HLA- DQA1, HLA-DQB1 and HLA-G 14 bp insertion/deletion polymorphism among women with RPL. Conclusions. Сhanges in the major hystocompatibility complex genes can cause the failure of a woman’s reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In total, forty-four studies were enrolled for regarding the association of RM and 14 bp ins/del variant, six studies for rs1063320, and four citations for rs1707, rs1710, rs17179101, rs17179108, rs9380142, and rs1610696, respectively. HWE analysis indicated that seven articles [20,21,42,45,48,50,63] deviated from statistical equilibrium in the control group, and two studies [31,33] cannot compute the p value of HWE because of unavailable genotypic data. Moreover, the average NOS score of included studies was 7.14 (ranged from 5 to 9), indicating that most of the studies were of high quality.…”
Section: Eligible Study Identification and Selectionmentioning
confidence: 99%
“…In total, forty-four studies were enrolled for regarding the association of RM and 14 bp ins/del variant, six studies for rs1063320, and four citations for rs1707, rs1710, rs17179101, rs17179108, rs9380142, and rs1610696, respectively. HWE analysis indicated that seven articles [20,21,42,45,48,50,63] deviated from statistical equilibrium in the control group, and two studies [31,33] cannot compute the p value of HWE because of unavailable genotypic data. Moreover, the average NOS score of included studies was 7.14 (ranged from 5 to 9), indicating that most of the studies were of high quality.…”
Section: Eligible Study Identification and Selectionmentioning
confidence: 99%